2021
DOI: 10.1186/s13006-021-00372-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of prenatal counselling and immediate postnatal support with early initiation of breastfeeding in Uttar Pradesh, India

Abstract: Background Timely initiation of breastfeeding, also known as early initiation of breastfeeding, is a well-recognized life-saving intervention to reduce neonatal mortality. However, only one quarter of newborns in Uttar Pradesh, India were breastfed in the first hour of life. This paper aims to understand the association of community-based prenatal counselling and postnatal support at place of delivery with early initiation of breastfeeding in Uttar Pradesh, India. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
0
12
1
Order By: Relevance
“…During observation of nutrition service delivery, we found that only 17.6% facilities had dedicated space for counselling and although most pregnant women received counselling about their own diet, only 10% women were counselled on breastfeeding. This is an important missed opportunity as previous studies have shown that counselling during pregnancy have significant positive impact on initiation and duration of breastfeeding [ 26 , 27 ]. It is important to note that only half of the mothers received 4 ANC services which points to the need for improving health service utilization so that there are multiple opportunities to avail nutrition services.…”
Section: Discussionmentioning
confidence: 99%
“…During observation of nutrition service delivery, we found that only 17.6% facilities had dedicated space for counselling and although most pregnant women received counselling about their own diet, only 10% women were counselled on breastfeeding. This is an important missed opportunity as previous studies have shown that counselling during pregnancy have significant positive impact on initiation and duration of breastfeeding [ 26 , 27 ]. It is important to note that only half of the mothers received 4 ANC services which points to the need for improving health service utilization so that there are multiple opportunities to avail nutrition services.…”
Section: Discussionmentioning
confidence: 99%
“…Access to quality evidence-based maternal care is necessary to reduce maternal mortality and morbidity. However, the cost of delivery and post-natal care can affect the utilization of these services [ 15 ]. The results of the present study reported that all the pre-birth as well as post-birth respondents highlighted that the cost of maternal care was quite high and not affordable for all.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the percentage of EIBF becomes maximum amongst the mothers who received both prenatal counselling and postnatal support regardless of the place of delivery. 26 The main limitation of the present QI study was the lack of designated lactation nursing staff and lactation counsellor. The work of providing continuous support to the mother while SSC and monitoring was shared by the multiple staff members because of the nonavailability of a designated staff.…”
Section: Discussionmentioning
confidence: 93%
“…A recent study showed that the percentage of EIBF becomes maximum amongst the mothers who received both prenatal counselling and postnatal support regardless of the place of delivery. 26…”
Section: Discussionmentioning
confidence: 99%